Aflatoxin and protein content in 13 bean (Phaseolus vulgaris L.) varieties - Peña-Betancourt, Silvia Denise; Conde-Martínez, Víctor (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, the bean (Phaseolus vulgaris L.) is a highly consumed legume seed (11 kg per capita annually), so that its cultivation it ́s quite extensive in different regions. In this study we investigated the presence of aflatoxins in eight common bean varieties and five improved bean varieties, in addition to protein and moisture. In all the varieties tested, the moisture content showed large variations (from 6 to 16%), being 16% of the varieties studied outside the normal (
Keywords: Phaseolus vulgaris L.; Phaseolus coccineus L.; toxic and anti-nutritional substances